The Burden of Care of Gay Male Carers Caring for Men Living With HIV/AIDS - Ian Munro RN, PhD; Karen-Leigh Edward RN, PhD (American Journal of Men's Health, 2010)
Objective: The notion of caregiver ‘burden’ has been used as a term that refers to the financial, physical and emotional effects of caring. This Australian 2002 research investigated the caregiver burden of HIV/AIDS on the gay male carers of gay men with the disease. Methods: This study was a phenomenological inquiry and employed van Manen’s approach to content analysis. Data saturation occurred at twelve participants. Results: The findings produced carer themes relating to coping with the burden of care of a person living with HIV/AIDS (PLWHA) in the context of living day-to-day with HIV/AIDS, coping with the last phase of AIDS toward death, saying goodbye and remembrance. Conclusion: Allocating resources to gay male carers such as; education, respite care, family therapy and cognitive-behavioral therapy (CBT) to address grief and stigma issues, has implications for how health services might reduce the burden of care for these carers.